Mitochondrial Dysfunction in Neurodegenerative Diseases: Exploring Therapeutic Approaches for Parkinson’s Disease - Mahar, Saifullah Khan; Amara; Yaseen, Khizer; Jan, Agha Mohammad Amin; Ali, Ammara (Indus Journal of Bioscience Research, 2025)
Parkinson ’s disease (PD) is a progressive neurodegenerative disorder characterized by the loss of dopaminergic neurons and the accumulation of misfolded α-synuclein protein aggregates. A central aspect of PD pathophysiology is mitochondrial dysfunction and the resulting oxidative stress, both of which contribute to neuronal degeneration and disease progression. A total of 121 PD patients were included in the sample, selected using snowball sampling techniques. Data were collected through structured interviews and medical records, ensuring the inclusion of demographic information, disease duration, disease stage, and current treatment regimens. The demographic analysis revealed that the majority of participants were male (53.7%), with the highest age group falling in the 60-69 years range (33.1%). The disease duration varied, with most patients (45.5%) being diagnosed within the last 5 years. The study also explored comorbidities, with hypertension (41.3%) being the most common, followed by diabetes (24.8%) and cardiovascular disease (16.5%). This study aimed to explore the relationship between mitochondrial dysfunction, oxidative stress, and clinical outcomes in PD patients, as well as to examine the potential influence of disease stage on treatment choices. A total of 121 patients from major hospitals in Pakistan participated in the study, with demographic data, including age, gender, disease duration, and stage of the disease, being collected. Statistical analysis, including correlation, multiple regression, and Chi-Square tests, revealed significant correlations between mitochondrial dysfunction, oxidative stress, and disease severity in PD. Oxidative stress exerted a stronger influence on outcomes and was identified as a major contributor in regression analysis. No significant association was found between disease stage and medication type. These results emphasize the importance of targeting mitochondrial dysfunction and oxidative stress. Future research should develop therapies to restore mitochondrial function and reduce oxidative stress to slow disease progression.